A baseline assessment of farm, household, gender and socioeconomic attributes in Bangladesh - Mishra, Ashok K.; Dela Rueda, Justin B.; Villanueva, Donald B.; Raviz, Jeny V.; Pede, Valerien O. (International Rice Research Institute, 2024)
The study highlights the agroecological and socioeconomic diversity within the AMD coverage areas. Key findings indicate that households rely heavily on farming for their income with rice and mung beans being the dominant crops while livestock and aquaculture raising are evident. Productivity trends indicate that small farms outperform larger ones, with Boro rice yielding higher returns than Aman rice and mung bean farmers generating decent returns. Mechanization levels are nearly universal for land preparation but remain minimal for other activities like crop establishment and pest, disease and weed management. Mechanization opportunities in mung bean production remain underutilized. Climate risk exposures significantly affect production leading to substantial losses partly explained by low to non-adoption of climate adaptation and mitigation practices. Household and women's participation in community organizations and activities is notably low and access to support services is limited, posing challenges to achieving development objectives. Gender dynamics reveal the shift towards joint household decision making but traditional gender roles remain prevalent.